The education of the Indian in Natal,(1860-1947). Volume Two - Cooppan,Somarsundarum (Department of Philosophy, 2023)
This historical, critical study of "The Education of the Indian in Natal 1860•1947", in two volumes, is presented as a thesis in fulfilment of the requirements for the degree of Doctor of Philosophy in the faculty of 1:ducation at the University of ; Cape Town. The study was commenced in April, 1943 and carried on as a full aimed engagement, except for an unavoidable total suspension of work during the whole of 1945, part of 1946 and part of 194?. The greater part of the collection and collation of the material had been completed by the middle of 1944. The final draft of the chapters covering the period 1860-1894 was written and typed in the second half of 1944. Tae drafting of the chapters covering the period 1895- 1g10 was not undertaken till March 1946. This break in the continuity of the work might have slightly affected the style of the subsequent chapters. On the other hand, the interval was a blessing in disguise for it placed me in possession of certain original correspondence, press cuttings and notes belonging to the late Mr. H.L.Paul, an Indian interpreter of the Magistrate's Court, Durban, which threw considerable light upon the educational development of this period, and in which Mr. Paul himself played no mean part. Had it not been for this additional material the story of the growth of Indian education in this period would not have been as full as it is now, owing to the scantiness of material from official sources. After another breaks, further research and final drafting of the chapters covering the period 1910-1947 was regularly undertaken from about May 1947. Originally it was intended to carry the study up to the year 1943, but it has now been extended up to the year 1947. I have incorporated various new items of information published since 19 43 and also various new developments that have taken place since then and brought the study as nearly up to date as it as possible. It is hoped that this may compensate for ~ the long delay in the completion of the project. When I commenced this project there was no record if, of any similar work having been undertaken by any other person. But in July 1944 my attention was drawn to a thesis on the same topic submitted by pne H.D. x:a·nnemeyer for the degree or Master or Education at the University of Witwatersrand in April 1944 (1) This work covers the period 1860...;.1937. Except for occasional· similarities which are unavoidable, there are many respects in which our two works are different, and, I believe, that my own study throws a certain amount or new light on the subject. Again, in February, 1948 I was shown another thesis on the same field presented for the Master or Education degree of the University of South Africa in November 1946, by one C.Kuppusami( 2 ). Here again our arrangement and treatment of the subject-are different.